The Influence of Live Streaming, Price Discount, and Online Customer Review on Purchase Intention of Somethinc Products (A Study on Students of UPN “Veteran” East Java as Consumers of Somethinc Products Shopping on Shopee) - Wirda Fitria Sahila; Siti Ning Farida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the significant influence of Live Streaming, Price Discount, and Online Customer Review both simultaneously and partially on consumer Purchase Intention for Somethinc products on the Shopee platform. This research is associative in nature with a quantitative approach. Variable measurement was conducted using a Likert scale with criteria ranging from strongly disagree to strongly agree. The sampling technique employed was probability sampling with a simple random sampling approach. The population in this study consists of active students at UPN "Veteran" East Java, with a sample of 100 respondents who have Shopee accounts and have purchased Somethinc products at least twice. Data collection was conducted using a questionnaire distributed via Google Form. The data analysis technique used SPSS version 27. The results of the study show that the variables Live Streaming, Price Discount, and Online Customer Review simultaneously have a significant effect on Purchase Intention. Partially, the variables Live Streaming and Price Discount have a significant effect on Purchase Intention, while the Online Customer Review variable does not have a significant effect on consumer Purchase Intention for Somethinc products on Shopee.